Visualization approach to effective decision making on hydrological data - Ahmad, Faudziah; Ahmad, Khairul Bariah; Othman, Azliza (International Association of Computer Science and Information Technology Press (IACSIT Press), 2011)
Temporal data is by nature arranged according to the sequence of time where the order of the data is very significant.Thus in order to visualize a temporal data, the order of the data has to be preserve that will show certain trends or temporal patterns. Most visualization technique however uses technical visual representation such as bar chart and line graph. This approach is suitable and can be easily comprehended only by technical users. In order to reduce the learning curve in understanding the prototype develop and facilitate decision making, metaphor based visualization approach was used for representing temporal hydrological data. To evaluate the correct of decision making similarity test was conducted by using data mining approach, specifically incorporating case-based reasoning. The test case or new data was compared with the case extracted from previous operation data and the case closely was examined by exploring the detailed data. Results were evaluated through usability testing and similarity testing. The prototype was demonstrated to a group of users specifically three DID staff involved with the dam operation directly and indirectly. The feedbacks received from the users are positive where the interface objects used took a short time for them to learn and understand due to the familiarity of the representation. One look at the map, it will give them the overall picture of the situation patterns of the dam water level and rainfall around the catchments area according to the time frame chosen. The metaphorical representation based visualization is used as a basis to represent temporal and multi-variate data using icon based technique and colour code to enhance interface usability and usefulness. This type of representation can be easily understood by a non-expert from the domain. The visualization actually assists users in the process of decision-making by representing the patterns in form close to the mental model of a user by using metaphor.This help speed up data exploration thus decision-making process. In critical situation speed and accuracy is vital in the decision making process.